Studnia z Dąbrówki koło Poznania. Nowe źródła do badań nad początkami osadnictwa grodowego w Wielkopolsce - Pawlak, Ewa; Pawlak, Paweł; Makowiecka, Marzena; Makowiecki, Daniel; Milecka, Milecka; Rennwanz, Joanna (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
In 2021, research was carried out which, despite its small scope, yielded a number of interesting discoveries related to Dąbrówka stronghold settlement. The most significant was the discovery of a well with preserved oak casing, built no earlier than in 870 and no later than in the mid-870s. This sequence of dates, however, covers a long period from 855 (-0/+8) to 878 (-7/+8) and indicates the use of raw material for developments of much greater scope. The only project that involved the use of such masses of wood at the time was the construction of a stronghold. From within the casing comes a wooden bucket with hoops, the ends of which are decorated with representations of animal heads. The research has also revealed a piece of an axe, related to a bradatica-type double-edged weapon, and an appliqué in the form of a rosette with numerous parallels among products of the Avar culture and assemblages of mixed Avaro-Slavic nature.